Flipbook E-Module-Assisted 8e Learning Cycle Model on Improving High School Students’ Concept Mastery on Heat and Heat Transfer Material - Putri, Novia Ananda; Liliawati, Winny; Efendi, Ridwan (Department of Physics Education, Universitas Mataram, 2024)
Physics concept mastery is a demand that is to be achieved in learning at high school level. In addition, the development of 21st century technology requires teachers to be able to use technology in organising students to learn. This study aims to determine the effect of flipbook e-module-assisted 8e learning cycle model on improving high school students' concept mastery on heat and heat transfer material. This research is a quantitative study that uses quasi experimental design with Nonequivalent Control Group. Participants included 70 students of class XI (eleventh graders) in a MAN (State Islamic High Schools) in Bandung, which were selected using convenience sampling technique. Data collection was done through a pretest and a posttest encompassing as many as 12 items of two tier multiple choice questions on concept mastery. The data analysis used N-gain test to determine the increase in concept mastery, and Mann Withney test to determine the effect of flipbook e-module-assisted 8e learning cycle model on students' concept mastery. The results showed that there was an increase in concept mastery after treatment was given, that is, by 0.60 (moderate). There is a significant difference in the improvement of the concept mastery between the experimental class and the control class, especially in the cognitive aspect of C3, which is 54.65%, and the material aspect of heat transfer, which is 36.42%. In conclusion, flipbook e-module-assisted 8e learning cycle model has an effect on improving students' concept mastery.